2016
DOI: 10.1007/s10661-016-5269-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating chlorophyll and nitrogen levels of mangroves at Al-Khor, Qatar: an integrated chemical analysis and remote sensing approach

Abstract: Mangroves are unique ecosystems that dominate tropical and subtropical coastlines around the world. They provide shelter and nursery to wide variety of species such as fish and birds. Around 73 species of mangroves were recognized around the world. In Qatar, there is only one mangrove species Avicennia marina that is predominant along the northeastern coast. Assessing the health of these valuable ecosystems is vital for protection, management, and conservation of those resources. In this study, an integrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
0
0
Order By: Relevance
“…The inversion results for the chlorophyll content from the red-edge position model in this study were similar to those reported in 2015 by Heenkenda from his examination of the relationship between the observed and predicted chlorophyll values from the Rapid Creek mangrove forest in Darwin, Australia, using the red edge [7]. In 2016, Al-Naimi et al used the Landsat 8 satellites to estimate the chlorophyll content of mangroves at Al-Khor, Qatar, with a model that had a maximum R 2 value of 0.6016 [62]. In this study, we improved the precision of the model for estimating the chlorophyll content of mangroves.…”
Section: Discussionsupporting
confidence: 84%
“…The inversion results for the chlorophyll content from the red-edge position model in this study were similar to those reported in 2015 by Heenkenda from his examination of the relationship between the observed and predicted chlorophyll values from the Rapid Creek mangrove forest in Darwin, Australia, using the red edge [7]. In 2016, Al-Naimi et al used the Landsat 8 satellites to estimate the chlorophyll content of mangroves at Al-Khor, Qatar, with a model that had a maximum R 2 value of 0.6016 [62]. In this study, we improved the precision of the model for estimating the chlorophyll content of mangroves.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, Oman lost 14.3% (24 ha) of natural mangroves from 1996 to 2020 (Bunting et al, 2022). This was mainly due to the growth of urban development activities related to coastal infrastructure and industrial expansion (Milani, 2018;Arshad et al, 2020;Aljenaid et al, 2022;AlQahtany et al, 2022), in addition to climate change impacts (Al-Naimi et al, 2016;Almahasheer, 2018;Blanco-Sacristań et al, 2022). However, some studies reported stable to slight increases in mangrove cover over the same period in the GCC countries (Almahasheer et al, 2016;Almahasheer, 2018;Milani, 2018).…”
Section: Contribution Of Remote Sensing Studiesmentioning
confidence: 99%
“…Despite the well-known importance of mangroves in the GCC region, these highly complex, vulnerable and fragile forest ecosystems are facing a wide variety of threats, including stressors driven by climate change and anthropogenic land use change activities (Burt, 2014;Al-Naimi et al, 2016;Almahasheer, 2018;Blanco-Sacristań et al, 2022). Specific threats to mangrove ecosystems are important to understand and can be identified through the use of remotely sensed data.…”
Section: Major Findingsmentioning
confidence: 99%
See 2 more Smart Citations